The Host Autophagy During Toxoplasma Infection - Wu, Minmin; Cudjoe, Obed; Shen, Jilong; Chen, Ying; Du, Jian (Frontiers in Microbiology, 2020)
Autophagy is an important homeostatic mechanism, in which lysosomes degrade and recycle cytosolic components. As a key defense mechanism against infections, autophagy involves in the capture of intracellular parasites and routing them for clearance. However, these intracellular parasites such as Toxoplasma gondii, have developed several evasion mechanisms to manipulate the host cell autophagy for their growth and establish a chronic infection. This review provides an insight into the autophagy mechanism used by the host cells in the control of Toxoplasma gondii and the host exploitation by the parasite. First, we summarize the mechanism of canonical and non-canonical autophagy pathways. Then we discuss the interplay between Toxoplasma gondii and autophagy; how host cell autophagy targets Toxoplasma gondii for destruction and how the parasite blocks and exploits this process for its survival.